2004
DOI: 10.1111/j.1365-2249.2004.02409.x
|View full text |Cite
|
Sign up to set email alerts
|

Early deficit of lymphocytes in Wiskott–Aldrich syndrome: possible role of WASP in human lymphocyte maturation

Abstract: SUMMARYWiskott-Aldrich syndrome (WAS) is an X-linked platelet/immunodeficiency disease. The affected gene encodes WASP, a multidomain protein that regulates cytoskeletal assembly in blood cells. Patients have recurring infections, and their lymphocytes exhibit deficient proliferative responses in vitro . We report an evaluation of peripheral blood lymphocytes of 27 WAS patients, aged one month to 55 years. Whereas NK cells were normal, a significant deficit of T and B lymphocytes was observed. The number of ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 38 publications
(38 reference statements)
6
78
1
1
Order By: Relevance
“…We could show that WBD is capable not only of confirming the previously described hematopoietic alterations occurring in these individuals 4, 5, 6, 7, 9, 10, 17 but also of providing novel information on the hematopoietic landscape of these diseases. Indeed, together with the known defects in B cell contribution (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…We could show that WBD is capable not only of confirming the previously described hematopoietic alterations occurring in these individuals 4, 5, 6, 7, 9, 10, 17 but also of providing novel information on the hematopoietic landscape of these diseases. Indeed, together with the known defects in B cell contribution (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Although WASP deficiency affects the functions of both lymphoid and myeloid cells, results obtained from the follow-up of WAS patients who underwent HLAmatched hemopoietic stem cell transplant, and from the analysis of WAS patients with spontaneous genetic reversion, indicate that WASP expression confers a selective growth advantage to T cells only (20,21). Consistently, it has been shown that WAS patients have a reduction in the numbers of circulating T lymphocytes, especially within the naive compartment (22). WAS patients suffer from recurrent infections caused by encapsulated bacteria, viruses, and fungi (19), suggesting an impairment in cellular-mediated immunity.…”
Section: W Iskott-aldrich Syndrome (Was)mentioning
confidence: 80%
“…This study showed that WASP expression is confined to a subset of the patient's memory T cells; his naive T cells are WASP-negative (M. I. Lutskiy et al, manuscript in preparation). For infants with WAS, although their lymphocyte numbers differ from normal, memory T cells are largely absent as in normal infants due to predominance of naive T cell populations (38). Further study of the mechanism of discordant WASP expression is needed particularly for the relatively frequent IVS 6 (ϩ5) gϾa genotype.…”
Section: Discussionmentioning
confidence: 99%